A Magyar Királyi Honvédség Kárpátalján - Suba, János (Közép-Európai Közlemények, 2016)
The Lower Carpathians returned to Hungary in two steps. After the 2nd Vienna Decision the mother country got back a part of Northern Hungary, including the South of the lower Carpathians, where mostly Hungarian population lived, along with Ungvár, Munkács and Beregszász. This part accounted for more than one fifth of the Lower Carpathians. For the Hungarian party it was essential to own the territory situated in the West of the Ung River’s valley. Ungvár was located near the border and the railway lines to Poland had to be secured as well. The Hungarian army occupied the Ung valley and Slovakia respected the new border. The Lower Carpathians militarily belonged to the administrative territory of the 8th Army so the corps who stationed here were also subordinated to it. The border was monitored by the patrols and protected by border guards. The armed forces were being developed continuously; this study describes this process and reviews the military corps deployed in the Lower Carpathians.